Simultaneous acid red 27 decolourisation and bioelectricity generation in a (H-type) microbial fuel cell configuration using NAR-2 - Kardi, Seyedeh Nazanin (Springer Verlag, 2016)
Microbial fuel cells (MFCs) represent one of the most attractive and eco-friendly technologies that convert chemical bond energy derived from organic matter into electrical power by microbial catabolic activity. This paper presents the use of a H-type MFC involving a novel NAR-2 bacterial consortium consisting of Citrobacter sp. A1, Enterobacter sp. L17 and Enterococcus sp. C1 to produce electricity whilst simultaneously decolourising acid red 27 (AR27) as a model dye, which is also known as amaranth. In this setup, the dye AR27 is mixed with modified P5 medium (2.5 g/L glucose and 5.0 g/L nutrient broth) in the anode compartment, whilst phosphate buffer solution (PBS) pH 7 serves as a catholyte in the cathode compartment. After several electrochemical analyses, the open circuit voltage (OCV) for 0.3 g/L AR27 with 24-h retention time at 30 °C was recorded as 0.950 V, whereas (93 %) decolourisation was achieved in 220-min operation. The maximum power density was reached after 48 h of operation with an external load of 300 Ω. Scanning electron microscopy (SEM) analysis revealed the surface morphology of the anode and the bacterial adhesion onto the electrode surface. The results of this study indicate that the decolourisation of AR27 dye and electrical power generation was successfully achieved in a MFC operated by a bacterial consortium. The consortium of bacteria was able to utilise AR27 in a short retention time as an electron acceptor and to shuttle the electrons to the anode surface for bioelectricity generation.